Stunting Reduction Policy Implementation: Examining Local Regulations and Programs in the Special Region of Yogyakarta through Grindle's Theory - Bambang Soetono; Yulianto; Evi Satispi; Ade Siti Barokah (SWATANTRA, 2026)
This article examines the implementation of stunting reduction policy convergence in the Special Region of Yogyakarta (DIY) through a qualitative descriptive design grounded in Grindle’s policy implementation model and enriched by a collaborative governance perspective. The manuscript aligns with the dissertation evidence base by using in-depth interviews, focus group discussions (FGDs), and analysis of national and subnational policy documents gathered across provincial, district/city, subdistrict, and village levels during the 2018-2023 policy period. The data were analyzed through thematic coding assisted by NVivo in order to trace the interaction between policy content, policy context, and the collaborative mechanisms that shape implementation outcomes. The findings show that DIY’s relatively low stunting prevalence does not eliminate substantive implementation gaps. The most persistent constraints are fragmented intersectoral coordination, limited data integration and interoperability, uneven institutional capacity across localities, and variation in the quality of collaboration among state and non-state actors. At the same time, DIY’s special governance arrangement, local leadership, village-level convergence forums, and pentahelix engagement create room for contextual adaptation. The article argues that convergence should be understood not merely as program alignment, but as an adaptive implementation process within multi-level governance. Empirically, the study explains why a comparatively successful province still faces structural coordination problems; theoretically, it refines Grindle’s model by emphasizing the importance of multilevel collaboration, policy learning, and local contextualization.